Experimental investigation, modelling and simulation of rate-dependent response of 1–3 ferroelectric composites. (March 2016) - Maniprakash, S.; Jayendiran, R.; Menzel, A.; Arockiarajan, A.
Abstract: Further development and design of piezoelectric composites enhances the improved use of piezoelectric materials and devices by overcoming their brittleness. In order to engineer this class of materials and to predictably simulate its behaviour, a computationally efficient constitutive model is established in this paper. This contribution deals with the development of a model for piezoelectric composites to capture their effective behaviour. We first discuss a three-dimensional fully coupled electromechanical rate-dependent model for the response of ferroelectric ceramics. Secondly, a simple homogenisation approach is applied to capture the behaviour of composites for various volume fractions of PZT fibres under different loading frequencies. Following this, a finite element formulation is applied in order to study the behaviour of composites. Finally, these two approaches are compared with experimental results.